Impact of economic globalization on economic growth in the ECOWAS region - Mirian, Anyachebelu Uzoma (Indonesian Journal Publisher, 2025)
This paper examines the effects of economic globalization on Nigeria's economic development. Data for the analysis were obtained from the 2022 World Development Indicators (WDI), with annual figures transformed into quarterly intervals using E-Views software, version 9. The analysis utilized the panel random effects model as its core econometric method. Results reveal that economic globalization contributes positively and significantly to economic growth across the ECOWAS member states. In light of these findings, the study recommends that ECOWAS governments enhance investments in information and communication technology (ICT), promote trade liberalization, and attract more foreign direct investment. These strategies are expected to stimulate the development of productive sectors and drive sustainable growth across the region. Additionally, the study encourages ECOWAS nations to diversify their economic structures by reactivating underperforming industries, including agriculture, mining, and manufacturing, to elevate domestic production and expand export capacity. It is also advised that central banks within the region maintain stable exchange rate policies to support these initiatives. The contribution of this research lies in its empirical evaluation of the globalization-growth nexus within the ECOWAS framework, providing policymakers with evidence-based insights. By highlighting sectoral reforms and regional policy alignment, the study offers a roadmap for inclusive and sustained economic development.